The impact of neuromyelitis optica on the recognition of emotional facial expressions: A preliminary report - Cardona Londoño, Juan Felipe (2014)
Although neuromyelitis optica (NMO) is classically recognized as an affectation of optic nerves and spinal cord, recent reports have shown brain atrophy and cognitive dysfunction in this condition. Importantly, emotion-related brain regions appear to be impaired in NMO. However, no studies of NMO’ emotional processing have been published. The goal of the current study was to investigate facial emotion recognition in 10 patients with NMO and 10 healthy controls by controlling for relevant cognitive factors. Consistent with previous reports, NMO patients performed poorly across cognitive domains (divided attention, working memory, and information-processing speed). Our findings further evidence the relative inability of NMO patients to recognize negative emotions (disgust, anger, and fear), in comparison to controls, with these deficits not explained by other cognitive impairments. Results provide the first evidence that NMO may impair the ability to recognize negative emotions. These impairments appear to be related to possible damage in brain regions underling emotional networks, including the anterior cingulate cortex, amygdala, and medial prefrontal cortex. Findings increased both our understanding of NMO’s cognitive impairment, and the neural networks underlying negative emotions.